Agrarian Citizenship and the Protection of Farmers' Rights in Indonesia's Forest Areas - M. Nazir Salim; Rahardian Rahmansani; Rohmat Junarto (Yustisia, 2025)
The Ministry of Forestry designates Cimrutu Village, Central Java, Indonesia, as a forest area under the "concession" of Perhutani, a state-owned forestry company. This situation is detrimental to society as most of the community's agricultural rights and economic access to land are obstructed by the Indonesian Ministry of Forestry's policy forbidding communities from possessing land rights in forested regions. This study investigates the historical context of land tenure conflicts and disputes over land claims by communities governed and subsequently asserted by the State Forestry Public Company. Using a spatial analysis approach, the data-gathering technique was executed qualitatively on community-controlled land. The study's findings indicate that the community in Cimrutu Village has possessed the land since 1967, yet prolonged tenure disputes have arisen, exacerbating poverty due to farmers' restricted access. Urgent policy advancements are required for the welfare of individuals, specifically the removal of residential and livelihood lands from forested regions to ensure access to economic opportunities.